“Los procesos de reclutamiento y selección del personal administrativo y de servicio en el Distrito de Educación 06d04 Colta-Guamote, y su influencia en el desarrollo institucional periodo 2014 – 2015” - Quishpe Chicaiza, Luis Edgar (2017)
This research aims to guide "The processes of recruitment and selection of administrative and service personnel in the Colta-Guamote Education District 06D04 and its influence on the institutional development 2014 - 2015 period" in those processes in which we find inconsistencies, disagreements, The violation of the laws and regulations in force in the recruitment and selection processes of personnel in this district. In the process of administrative management of human talent submitted to the correct application of the recruitment and selection of administrative staff in the Colta-Guamote Educational District, there are a number of drawbacks to which the current Laws and Regulations try to cope, with the purpose of improving their professional performance through knowledge about the processes of recruitment and selection of the administrative staff of the district and to advise the responsible educational actors for the efficient performance. But not only has the irregularity of the application of the laws and their current regulations in the processes of recruitment and selection of administrative staff affected the education sector. In order to know if the administrative officials can fulfill the appropriate profiles and processes in the coming periods, it is also concerned with generating spaces and adequate conditions for compliance by the insecurity generated by other officials, price variations Of the cost-benefit results, at the time of training, leveling or accompaniment: all of them are factors that affect the good development of quality, warmth and efficiency in the Colta-Guamote Educational District. The objective of this thesis is to define the elements of adequate application of the process of recruitment and selection of personnel that in general allows to take into account the laws and their regulations. In addition, to analyze the factors that influence the processes of recruitment and selection of the administrative staff of the Colta-Guamote educational district in institutional development. Also, it will be of paramount importance to diagnose and identify the processes of recruitment and selection of administrative and service personnel, the most solid to determine the success of the application of a new model of educational management.